Transport and logistics potential and prospects of using the Chabahar Port for Central Asian countriesТранспортно-логистический потенциал и перспективы использования порта Чабахар для стран Центральной Азии - Zhekenov, D.; Jakubayeva, S. (Journal of Oriental Studies, 2023)
It is well known that almost a third of the developing countries of the world with no direct access to the sea are located in Europe and Central Asia. Many people in these countries are engaged exclusively in agriculture to survive, but the lack of access to the sea creates an additional burden for the development of agriculture and trade. According to a World Bank study, the cost of transporting goods imported from these developing countries is twice as high as the cost of transportation to their coastal neighbors. Tariffs, border checkpoints and undeveloped infrastructure lead to vehicle delays and further increases in trade costs. The purpose of the study is to study the potential of the Iranian port of Chabahar, prospects and trends in the development of transport and corridor routes, which are among the transit opportunities of the Central Asian states. The Central Asian countries are located in an isolated (land-locked area) region that has no direct access to the sea, although raw materials are located in the heart of Eurasia, in an area rich in natural resources. From an isolated zone (land-locked area), Central Asian countries need to establish transport and transit corridors to turn into a land-linked zone, this goal is of strategic importance on the agenda of all Central Asian countries, including Kazakhstan, effectively using the territory located in the periphery of East and West, North and South for dynamic economic development. In the era of globalization, at one time isolated from the outside world due to Western sanctions, Iran is now becoming a geopolitically active actor, rationally using its "sea power". It should also be noted that recent changes in the political scene, especially the war between Russia and Ukraine, are becoming a trigger factor for the development of these alternative transport and corridor projects. As a research methodology, the method of data analysis (secondary data analysis) is used, including the method of studying contracts and declarations, other official documents and data (documentary method analysis). In addition, in accordance with the relevance of the topic, the content analysis method was used during the analysis of interviews with government representatives and ranking of news site data. The source base of the research work is based on research conducted in English-speaking, Russian-speaking academic communities in the field of international relations. Funding: The research in the article was carried out with grant funding from the Ministry of Science and Higher Education of the Republic of Kazakhstan within the framework of the AR19679313 project “Competitiveness of transit and transport potential of Kazakhstan in the conditions of formation of alternative transport corridors”. Keywords: Central Asian States, Iran, transport corridors, Chabahar port, international North-South transport corridor